giúp mk vs
x mũ 2 -2xy +5y mũ 2 +8y -25
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(M=6x^2+9xy-y^2-5x^2+2xy=x^2+11xy-y^2\)
b: \(N=3xy-4y^2-x^2+7xy-8y^2=-x^2+10xy-12y^2\)
a) \(\frac{7^3.5^8}{49.25^4}=\frac{7^3.5^8}{7^2.\left(5^2\right)^4}=7.\frac{5^8}{5^8}=7\)
b) \(\frac{3^9.25.5^3}{15.625.3^8}=\frac{3.3^8.5^2.5^3}{3.5.5^4.3^8}=\frac{5^5}{5^5}=1\)
c) Đề hơi sai roi bạn oi
d) \(\left(\frac{2}{5}-\frac{1}{2}\right)^2+\left(\frac{1}{2}+\frac{3}{5}\right)^2=\left(\frac{-1}{10}\right)^2+\left(\frac{11}{10}\right)^2=\frac{1}{100}+\frac{121}{100}=\frac{61}{50}\)
1) x2 + x2y - y - 1
= x2( 1 + y ) - ( 1 + y )
= ( 1 + y )( x2 - 1 )
= ( 1 + y )( x - 1 )( x + 1 )
2) x2 + y2 - 2xy - 25
= ( x2 - 2xy + y2 ) - 25
= ( x - y )2 - 52
= ( x - y - 5 )( x - y + 5 )
3) ( 2x - 1 )( x2 + 2x - 1 ) - ( 1 - 2x )( x - 3 )
= ( 2x - 1 )( x2 + 2x - 1 ) + ( 2x - 1 )( x - 3 )
= ( 2x - 1 )( x2 + 2x - 1 + x - 3 )
= ( 2x - 1 )( x2 + 3x - 4 )
= ( 2x - 1 )( x2 - x + 4x - 4 )
= ( 2x - 1 )[ x( x - 1 ) + 4( x - 1 ) ]
= ( 2x - 1 )( x - 1 )( x + 4 )
4) a2 + x2 - 16 + 2ax
= ( a2 + 2ax + x2 ) - 16
= ( a + x )2 - 42
= ( a + x - 4 )( a + x + 4 )
\(P=2017-2x^2+4x-8y^2-8y\\ P=-2\left(x^2-2x+1\right)-2\left(4y^2+4y+1\right)+2021\\ P=-2\left(x-1\right)^2-2\left(2y+1\right)^2+2021\le2021\\ P_{max}=2021\Leftrightarrow\left\{{}\begin{matrix}x=1\\y=-\dfrac{1}{2}\end{matrix}\right.\)
a, \(x^2-4-3\left(x-2\right)=\left(x-2\right)\left(x+2\right)-3\left(x-2\right)=\left(x-1\right)\left(x-2\right)\)
b, \(x^2-xy+5y-25=\left(x-5\right)\left(x+5\right)-y\left(x-5\right)=\left(x+5-y\right)\left(x-5\right)\)
c, \(x^3+x^2-2x-8=\left(x-2\right)\left(x^2+2x+4\right)+x\left(x-2\right)=\left(x-2\right)\left(x^2+3x+4\right)\)
d, \(x^3-4x^2-8x+8=\left(x+2\right)\left(x^2-2x+4\right)-4x\left(x+2\right)=\left(x^2-6x+4\right)\left(x+2\right)\)
Trả lời:
1, x2 - 4 - 3 ( x - 2 )
= ( x2 - 4 ) - 3 ( x - 2 )
= ( x - 2 ) ( x + 2 ) - 3 ( x - 2 )
= ( x - 2 ) ( x + 2 - 3 )
= ( x - 2 ) ( x - 1 )
2, x2 - xy + 5y - 25
= ( x2 - 25 ) - ( xy - 5y )
= ( x - 5 ) ( x + 5 ) - y ( x - 5 )
= ( x - 5 ) ( x + 5 - y )
3, x3 + x2 - 2x - 8
= ( x3 - 8 ) + ( x2 - 2x )
= ( x - 2 ) ( x2 + 2x + 4 ) + x ( x - 2 )
= ( x - 2 ) ( x2 + 2x + 4 + x )
= ( x - 2 ) ( x2 + 3x + 4 )
4, x3 - 4x2 - 8x + 8
= ( x3 + 8 ) - ( 4x2 + 8x )
= ( x + 2 ) ( x2 - 2x + 4 ) - 4x ( x + 2 )
= ( x + 2 ) ( x2 - 2x + 4 - 4x )
= ( x + 2 ) ( x2 - 6x + 4 )
a)x²−2x−4y²−4ya)x²-2x-4y²-4y
=x²−2x−4y²−4y+2xy−2xy=x²-2x-4y²-4y+2xy-2xy
=(x²−2xy−2x)+(2xy−4y²−4y)=(x²-2xy-2x)+(2xy-4y²-4y)
=x(x−2y−2)+2y(x−2y−2)=x(x-2y-2)+2y(x-2y-2)
=(x+2y)(x−2y−2)=(x+2y)(x-2y-2)
b)x4+2x³−4x−4b)x4+2x³-4x-4
=x4+2x³+2x²−2x²−4x−4=x4+2x³+2x²-2x²-4x-4
=(x4+2x³+2x²)−(2x²+4x+4)=(x4+2x³+2x²)-(2x²+4x+4)
=x²(x²+2x+2)−2(x²+2x+2)=x²(x²+2x+2)-2(x²+2x+2)
=(x²−2)(x²+2x+2)=(x²-2)(x²+2x+2)
c)x³+2x²y−x−2yc)x³+2x²y-x-2y
=x²(x+2y)−(x+2y)=x²(x+2y)-(x+2y)
=(x²−1)(x+2y)=(x²-1)(x+2y)
=(x+1)(x−1)(x+2y)=(x+1)(x-1)(x+2y)
d)3x²−3y²−2(x−y)²d)3x²-3y²-2(x-y)²
=3(x²−y²)−2(x−y)²=3(x²-y²)-2(x-y)²
=3(x+y)(x−y)−2(x−y)²=3(x+y)(x-y)-2(x-y)²
=(x−y)[3(x+y)−2(x−y)]=(x-y)[3(x+y)-2(x-y)]
=(x−y)(3x+3y−2x+2y)=(x-y)(3x+3y-2x+2y)
=(x−y)(x+5y)=(x-y)(x+5y)
e)x³−4x²−9x+36e)x³-4x²-9x+36
=(x³−4x²)−(9x−36)=(x³-4x²)-(9x-36)
=x²(x−4)−9(x−4)=x²(x-4)-9(x-4)
=(x−4)(x²−9)=(x-4)(x²-9)
=(x−4)(x²−3²)=(x-4)(x²-3²)
=(x−4)(x+3)(x−3)=(x-4)(x+3)(x-3)
f)x²−y²−2x−2yf)x²-y²-2x-2y
=(x²−y²)−(2x+2y)=(x²-y²)-(2x+2y)
=(x+y)(x−y)−2(x+y)=(x+y)(x-y)-2(x+y)
=(x+y)(x−y−2)
hok tốt nhé
k đi